Self-esteem, happiness and the therapeutic fad cycle - Ashley Frawley (The Routledge International Handbook of Global Therapeutic Cultures, 2020)
In this contribution, I explore strong parallels across emotions as social issues in terms of advocacy, rhetoric and marked tendencies to rise, expand and give way to new vocabularies which nonetheless mark out very similar claims. In particular, I sketch out the cyclic nature of therapeutic fads surrounding self-esteem and happiness. As self-esteem was questioned as a panacea for social problems, happiness emerged as a powerful new discourse that performed very similar functions. Focusing on these cases, I draw on my earlier research on the construction of happiness as a social problem (Frawley, 2015, 2018) and Hewitt’s (1998) study of self-esteem to illustrate a growing tendency to problematise apparently positive emotional signifiers. Beginning with a discussion of fads and social problem cycles, I move to a discussion of ethnopsychology, or cultural assumptions about human psychology and human nature. I then describe key aspects of therapeutic fad cycles focusing on happiness and self-esteem as problematised positive emotional signifiers, from a ‘prehistory’ phase to discovery, adoption, expansion and exhaustion.